Knowledge and Attitude of the Benenificiaries of Livestock Development for Livelihood Support (Ldls) Programme in Goat Farming in Wayanad District of Kerala, India - Chethan G.N; Senthil Kumar R; Rajkamal P.J and Chandra Mohan B (International Research Journal of Social Sciences, 2015)
A questioner survey was conducted among150 beneficiaries of Livestock Development for Livelihood Support (LDLS) programme to understand the knowledge and attitude of the LDLS programme beneficiaries in goat farming in Wayanad district of Kerala state. The study revealed that majority of the beneficiaries had moderately favourable attitude (42.67%) towards goat farming and also moderately knowledgeable (42.00%) in goat farming. Further investigation on beneficiaries’ knowledge level revealed that only few beneficiaries had adequate knowledge about breeding, housing and health care aspects of goat farming. Comparatively higher proportion of beneficiaries had adequate knowledge about feeding and managemental practices of goats.